GC/MS Analysis of Fatty Acids on Pliek U Oil and Its Pharmacological Study by Molecular Docking to Filaggrin as a Drug Candidate in Atopic Dermatitis Treatment. (3rd November 2019) - Earlia, Nanda; Muslem; Suhendra, Rivansyah; Amin, Mohamad; Prakoeswa, C. R. S.; Khairan; Idroes, Rinaldi
Abstract : Analysis of fatty acid contents and pharmacological properties of Pliek U oil was performed. Fatty acids were analyzed by gas chromatography-mass spectrometry (GC-MS), and pharmacological properties based on its potential on filament-aggregating protein (filaggrin) were studied with bioinformatics approach by the reverse docking technique using palmitic acid as a control compound. Two Pliek U extracts, namely, Pliek U oil (PUO) and ethanolic Pliek U oil extract (EPUOE), were prepared. The GC-MS results revealed that lauric acid, myristic acid, palmitic acid, and oleic acid are the predominant fatty acids, with lauric acid being the abundant one in all Pliek U oil extracts. The reverse docking technique results showed that oleic acid had the most stable interaction to filaggrin with the lowest binding affinity (−6.1 kcal/mol). Oleic acid and palmitic acid have one same side binding to filaggrin on amino acid LEU D75. These findings indicated that oleic acid has the best potential to be used as a drug candidate in atopic dermatitis treatment.